TECHNOLOGICAL PARAMETERS OF SLUGS CASTING OF GREY CAST IRON BY FROSTING - E. I. Marukovich; V. S. Mazjko; V. P. Grusha (Литьë и металлургия, 2009)
The relation of geometrical parametres of casting with technological ones is shown. The monogram for definition of basic technological parametres of obtaining of castings by the method of continuously-cyclic iterative casting by freezing-up is presented.